THE AXES LITHIC WORKSHOP OF UCHPAPANGAL FORMATIVE, HUALLAGA VALLEY, PERUVIAN AMAZON - van Dalen Luna, Pieter (2014)
In this paper we realize the discovery and analysis of a lithic axes development workshop in Lower Huallaga, in Ushpapangal site, which is perhaps the first lithic workshop specialized in this type of device reported to date in the Peruvian Amazon. Emphasis is placed on the technological aspects of the production and the economic and social implications of their exchange, in an interregional perspective.